Pengaruh Intellectual Capital dan Leverage Terhadap Nilai Perusahaan Dengan Variabel Profitabilitas Sebagai Intervening Pada Jakarta Islamic Indeks 30 (Jii 30) Periode 2016-2022 - Azizah, Laila Nur; Kabib, Nur (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2024)
This research aims to determine "The Influence of Intellectual Capital and Leverage on Company Value with Profitability Variables as Intervening in Jakarta Islamic Indks 30 (Jii 30) 2016-2022". The JII 30 company share price index, in particular, is known for 2016-2022 to experience simultaneous share price fluctuations. This is thought to be the influence of the Covid-19 virus which has spread to the world economic situation. Consumption has decreased drastically, causing company profits to decrease. Automatically, the company's share price weakens. This type of research is quantitative research with a population of Semarang district residents. The data obtained is then processed using tools and then processed using IBM SPSS 21. The results that have been obtained from this research explain that the results of this research test show that: Variable intellectual capital has a positive and significant effect on company value. The intellectual capital variable has a positive and significant effect on profitability. The leverage variable has a negative and insignificant effect on company value. Variable leverage has a negative and insignificant effect on profitability. The profitability variable has a negative and insignificant effect on company value. Variable intellectual capital cannot mediate company value on profitability. Variable leverage cannot mediate company value on profitability.